Surface Treatment of Perovskite Layer with Guanidinium Iodide Leads to Enhanced Moisture Stability and Improved Efficiency of Perovskite Solar Cells. Issue 14 (3rd June 2020) - Chavan, Rohit D.; Prochowicz, Daniel; Tavakoli, Mohammad Mahdi; Yadav, Pankaj; Hong, Chang Kook
Abstract: Interfacial engineering between the perovskite and hole transport layers has emerged as an effective way to improve perovskite solar cell (PSC) performance. A variety of organic halide salts are developed to passivate the traps and enhance the charge carrier transport. Here, the use of guanidinium iodide (GuaI) for interfacial modification of mixed‐cation (Cs) x (FA)1− x PbI3 perovskite films, which results in the formation of a low‐dimensional δ‐FAPbI3 ‐like phase on the 3D perovskite surface, is reported. The presence of this thin layer facilitates charge transfer at interfaces and reduces charge carrier recombination pathways as evidenced by enhanced carrier lifetimes and favorable interfacial band alignment. As a result, the power conversion efficiency of the control device is boosted from 19.22% to 20.07%, mainly due to improved open‐circuit voltage ( V oc ) and fill factor. Furthermore, the post‐treatment with GuaI improves the moisture stability of perovskite polycrystalline films and ambient stability of PSCs. Abstract : This article reports the interfacial modification of mixed‐cation (Cs) x (FA)1− x PbI3 perovskite films with guanidinium hydroiodide salt, which results in the formation of a low‐dimensional δ‐FAPbI3 ‐like phase on the 3D perovskite surface. The presence of this thin layer facilitates charge transfer at interfaces and reduces charge carrier recombination pathways. Consequently, the performance and moisture stability of the control devices is improved compared to the unmodified device.